1961
DOI: 10.1017/s0022172400038729
|View full text |Cite
|
Sign up to set email alerts
|

Some factors affecting preservability of freeze-dried bacteria

Abstract: 1. The use of sodium glutamate as a medium for freeze-drying Lact. bifidus significantly enhanced the stability of the dried product, especially the heat stability.2. The optimal concentration of sodium glutamate, as a drying medium, was found to depend on the bacilliary concentration; the higher the concentration of the bacilliary suspension used the higher was found to be the optimal concentration of the sodium glutamate.3. It was possible to classify various drying media according to the degree of sublimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1962
1962
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The existence of an optimal concentration of sodium glutamate was essentially similar to that seen in BCG and Lactobacillus bifidus (Cho & Obayashi, 1956;Obayashi & Cho, 1957;Ota, 1959;Obayashi et al 1961). Obayashi et al (1961) suggested that the concentration of sodium glutamate is related to the residual moisture content of the final product, and that for the preservation of the product there existed an optimum residual moisture content. They observed that the increase in the concentration of sodium glutamate tended to depress the sublimation during the drying in contrast to soluble starch and PVP, in which no such diminution of sublimation occurred with increase of the concentration.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The existence of an optimal concentration of sodium glutamate was essentially similar to that seen in BCG and Lactobacillus bifidus (Cho & Obayashi, 1956;Obayashi & Cho, 1957;Ota, 1959;Obayashi et al 1961). Obayashi et al (1961) suggested that the concentration of sodium glutamate is related to the residual moisture content of the final product, and that for the preservation of the product there existed an optimum residual moisture content. They observed that the increase in the concentration of sodium glutamate tended to depress the sublimation during the drying in contrast to soluble starch and PVP, in which no such diminution of sublimation occurred with increase of the concentration.…”
Section: Discussionmentioning
confidence: 68%
“…In the second group, sodium glutamate was used in combination with soluble starch, polyvinylpyrrolidone (PVP) or sodium carboxymethyl cellulose (SCMC). According to Obayashi, Ota & Arai (1961) the first group of substances exert a sublimation-retarding effect, whereas the second group of substances, such as PVP and SCMC, rather have a sublimation-promoting property.…”
Section: Suspending Mediamentioning
confidence: 99%
“…Recently Obayashi, Ota and Shiro (1961) have suggested the use of polyvinylpyrrolidone as the protective colloid instead of dextran. From a limited experience, I have had good results using the K 30 fraction of polyvinylpyrrolidone with a mean molecular weight of 45,000 and also with Bayer's New Periston with a mean molecular weight of 11,500.…”
Section: Recent Advances In Freeze-dryingmentioning
confidence: 99%
“…It would be of interest to test these and other carbohydrates in the absence of peptone for protective properties at relatively high temperatures. Similarly, in view of tlie work of Miller and Goodner (1953), Greaves (1959), and Obayashi et al (1961, a trial of sodium glutamate as a preserving agent with tlie present drying technique should be profitable.…”
Section: Discussionmentioning
confidence: 95%
“…Proom and Hcmmons (1949) tested exposure at 80° C. to indicate the likehhood of long-term survival of desiccates at ambient temperatures. More recently Greaves (1959) and Obayashi, Ota and Arai (1961) have exposed desiccates at 100° C. for the same pitrpose. These tests are proving very useful particularly when they are compared with measurement of survival at temperatures near ambient level.…”
Section: Discussionmentioning
confidence: 99%